How best to ensure international digital competition cooperation - Christophe Carugati (Bruegel, 2023)
Large digital firms pose similar competition issues worldwide, such as promoting their own services over those of rivals, or imposing unfair terms and conditions. Competition authorities have opened several antitrust investigations and policymakers have proposed digital competition regulations to tackle these issues. G7 competition authorities have called for several years for international cooperation on digital markets. They want competition cases and laws around the world that are consistent and work together. However, the question of how this can be done remains. A toolbox for international cooperation in competition enforcement already exists, but it does not provide for cooperation in competition policy and has shortcomings in relation to competition enforcement. Current and proposed legislation targets the largest digital firms to tackle the characteristics of digital markets, such as multi-sidedness, and the same or very similar behaviours, such as self-preferencing. Legislation in different jurisdictions addresses these issues with similar rules. While there is some convergence, some rules diverge in substance and some are at high risk of divergence in interpretation. Inconsistency is thus likely to arise from a divergence of interpretation rather than substance. The solution would be to ensure a coherent approach to competition in digital markets. This could be done by developing a framework based on four elements: (1) adoption of common legal phases for future digital competition laws to ensure clarity; (2) adoption of a common legal interpretation through guidance drafted by international forums, such as the International Competition Network (ICN); (3) adoption of common technical requirements developed in the context of ICN technical workshops, when the rules require it; and (4) the implementation of an international monitoring committee within the ICN to evaluate whether competition authorities and courts enforce the rules consistently. The impact of the framework might be limited because of the non-binding nature of the approach, and the focus on specific competition-related legislation, excluding laws that can also address the issues, such as civil law. Countries can overcome these limitations if they are willing to cooperate to ensure a consistent approach.
Keywords: 330